Violence in Religious Sects: Visions and Reality - Kuznecovienė, Violeta (Sociologija. Mintis ir veiksmas, 2000)
The aim of the article is to analyze violence in religious sects. The analysis is built upon the Pierre Bourdieu's conception of symbolic power. The author develops her argument by, first, analyzing the conditions for possibility of violence in religious sects. The author argues that, second, symbolic violence is necessary for sects as a form of organization. Third, because of the role of violence in defining the organization, the author attempts to understand the mechanisms of power that recreate the form of the organization of the religious sects.
Keywords: sect; violence; symbolic power; Pierre Bourdieu